Surgical management of a compound odontoma. A case report with six months follow-up - Rodríguez-Landauro, Ana Juliet (2023)
Objective: To describe the conservative surgical management of a compound odontoma and its six-month follow-up in a pediatric patient. Case report: A female patient aged 9 years and 11 months with no history of dentoalveolar trauma attended the Dental Clinic of the Universidad Científica del Sur, Lima-Peru. Clinically. It was observed a delayed eruption of tooth 11. Panoramic and periapical radiographs showed a mixed radiolucent and radiopaque lesion compatible with compound odontoma. A conservative alveolar approach was performed under infiltrative local anesthesia, through a scalloped marginal incision. Then, decollation, conservative osteotomy and excision of three denticles were performed. Likewise, a careful curettage was carried out to prevent injury to vascular structures and dental germ. Subsequently, clinical, and radiographic controls were carried out at 1, 3 and 6 months after surgery; and it was found a favorable evolution. Conclusion: Early diagnosis and conservative surgical approach to compound odontoma were important to prevent retention and non-eruption of permanent teeth in a 9-year-old pediatric patient. The clinical and radiographic control after 6 months follow-up showed a favorable result of the treatment.